A diatomic iron nanozyme and its preparation method and application in enhancing the resistance to oxidative stress in organisms

Through the thermal reaction of adze nitrate, iron acetylacetonate and 2-methylimidazole in ethanol, combined with high-temperature annealing treatment, an iron diatomic nanozyme with stable configuration, biocompatibility and excellent anti-oxidative stress effect was prepared. It solves the deficiencies in the preparation and application of iron diatomic nanozymes in the existing technology, and achieves efficient decomposition of H2O2 and reduction of oxidative stress at inflammatory sites.

CN118682138BActive Publication Date: 2025-01-21HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411155107.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-21
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

It is difficult to prepare iron diatomic nanoenzymes with stable configuration, high biocompatibility and excellent antioxidant stress effects.

Method used

By dissolving zinc nitrate, iron acetylacetonate and 2-methylimidazole in ethanol, heating the reaction, a single-atom nanozyme is obtained, and then reacting with iron acetylacetonate and melamine again, and undergoing high-temperature annealing treatment, an iron diatomic nanozyme is prepared .

Benefits of technology

The prepared iron diatomic nanozyme has stable structure, good biocompatibility, catalase (CAT) antioxidant catalytic activity, can efficiently decompose H2O2, and significantly reduce the oxidative stress level at inflammatory sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118682138B_ABST
    Figure CN118682138B_ABST
Patent Text Reader

Abstract

The present invention discloses an iron diatomic nanozyme and a preparation method thereof and an application in enhancing anti-oxidative stress in an organism, and belongs to the field of diatomic nanozyme preparation and biomedical technology. The preparation method comprises the following steps: using zinc nitrate, 2-methylimidazole, ferric acetylacetonate, and melamine as precursors, using ethanol as a solvent, and obtaining an iron diatomic nanozyme by high temperature annealing. Beneficial effect: The iron diatomic nanozyme prepared by the present invention has excellent catalase catalytic activity, and can rapidly decompose hydrogen peroxide into oxygen under mild conditions, thereby effectively alleviating the overexpression of reactive oxygen species in the inflammatory site of the organism, and the generated oxygen is neutralized with the reactive oxygen species, reducing local oxidative stress, and further guiding macrophages to transform into the M2 phenotype, and finally achieving the purpose of alleviating inflammatory symptoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and biomedical fields of iron diatomic nanozymes, and specifically to an iron diatomic nanozyme with a high loading rate, good biocompatibility and excellent antioxidant properties, as well as a preparation method and application thereof. Background Art

[0002] Inflammatory diseases are often characterized by hypoxia, overexpression of reactive oxygen species (ROS), and excessive secretion of proinflammatory cytokines. These factors often lead to dysregulated inflammation and imbalanced macrophage phenotypes. Drugs can be used to regulate the microenvironment of the inflammatory site, such as producing oxygen (O 2 ) and neutralize reactive oxygen species (ROS), which can reduce local oxidative stress, thereby guiding macrophages to transform to the M2 phenotype and reducing inflammatory symptoms.

[0003] In recent years, with the rapid development of nanotechnology, various nanomaterials with enzyme-like activities (nanozymes) have attracted widespread attention due to their potential to treat oxidation-related diseases. Nanozymes not only have strong enzyme kinetic catalytic activity, but also have higher stability and lower cost than natural enzymes. Through rational design, these nanozymes with unique physicochemical properties and catalytic activity have shown great application prospects in biomedicine. Nanozymes can convert hydrogen peroxide (H 2 O 2 ) decomposes into water (H 2 O) and oxygen (O 2 ), thereby reducing ROS concentration and achieving the effect of anti-oxidative stress. This mechanism provides an ideal solution for the treatment of inflammatory diseases such as arthritis, diabetic trauma and eye inflammation. In particular, single-atom nanozymes, which have attracted much attention in recent years, can achieve maximum atomic utilization due to their well-defined electronic and geometric structures, exhibit excellent catalytic activity and selectivity, and enable researchers to study their structure-performance relationship at the atomic level.

[0004] Among various nanozymes, single-atom nanozymes based on iron-nitrogen-carbon (Fe–N–C) are the most favored by researchers because they have Fe–Nx coordination sites similar to iron porphyrins in metalloenzymes such as horseradish peroxidase (HRP), catalase, and cytochrome P450. This similarity helps to elucidate their catalytic mechanism and narrow the gap between nanozymes and natural enzymes. However, due to the high surface energy of single iron atoms, they easily aggregate to form metal nanoclusters, resulting in extremely low metal loading, which limits their catalytic activity to a certain extent. Studies have shown [S. Tian, ​​B. Wang etc. Dual-atom Pt heterogeneous catalyst with excellent catalytic performances for the selective hydrogenation and epoxidation, Nat. Commun., 2021, 12] that compared with single-atom iron nanozymes, the synergistic effect between two adjacent metal atoms can further improve the catalytic performance.

[0005] In particular, diatomic iron nanozymes show superior performance in mimicking catalase (CAT) activity due to the synergistic effect of the diatomic system, simplified rearrangement structure, and lower energy difference in the key transition state. Therefore, dual metal site catalysts are ideal candidates for antioxidant nanozymes. However, previous studies have not explored the application of iron diatomic nanozymes in CAT, nor have they studied their excellent CAT performance in anti-oxidative stress and its intrinsic structure-function relationship. It is of great significance to prepare ideal iron diatomic nanozymes and explore and develop their applications in high-performance anti-oxidative stress.

[0006] The Chinese patent application document with publication number CN116510777A discloses a plant microenvironment-responsive diatomic nanozyme and its preparation method and application. The preparation method includes: 1) mixing sodium ferric ethylenediaminetetraacetate and urea, calcining under nitrogen protection, and obtaining a mixture containing single-atom iron nanozymes; 2) adding a solvent to the mixture obtained in step 1) to dissolve, filter, and dry to obtain a single-atom iron nanozyme; 3) mixing the single-atom iron nanozyme obtained in step 2) with zinc salt, calcining under nitrogen protection, and obtaining a zinc-iron diatomic nanozyme solid. The nanozyme exhibits catalase-like activity under neutral conditions and can effectively decompose H 2 O 2 Generates oxygen and water. It exhibits peroxidase-like activity under acidic conditions, catalyzing H 2 O 2•OH is generated in situ on its surface, thereby achieving in situ degradation of phenolic acid. This patent can effectively improve the resistance of plants to phenolic acid stress, while zinc micro-fertilizer can provide plant nutrition and promote plant growth under adverse conditions. However, this patent does not disclose the iron diatomic nanozyme of the present invention, its preparation method, and its application in enhancing the anti-oxidative stress in organisms. Summary of the invention

[0007] The technical problem to be solved by the present invention is how to prepare an iron diatomic nanozyme with a stable configuration and high biocompatibility and anti-oxidative stress effect (CAT performance).

[0008] The present invention solves the above technical problems through the following technical means:

[0009] The present invention provides a method for preparing an iron diatomic nanozyme, comprising the following steps:

[0010] (1) Dissolve zinc nitrate, ferric acetylacetonate and 2-methylimidazole in ethanol and heat to react;

[0011] (2) centrifuging the solution after the reaction in step (1), taking the precipitate, washing it, and drying it to obtain a reddish-brown solid powder as a precursor for preparing the single-atom nanozyme;

[0012] (3) annealing and grinding the powder obtained in step (2) to obtain an iron single-atom nanozyme;

[0013] (4) dissolving the iron single-atom nanozyme obtained in step (3), ferric acetylacetonate and melamine in ethanol and heating them for reaction;

[0014] (5) centrifuging the solution after the reaction in step (4), taking the precipitate, washing, and drying to obtain a powder which is a precursor for preparing the diatomic nanozyme;

[0015] (6) annealing and grinding the powder obtained in step (5) to obtain an iron diatom nanozyme (Fe-NC);

[0016] In the step (1), the ratio of the mass of zinc nitrate, ferric acetylacetonate, and 2-methylimidazole to the volume of ethanol is (3-6) g: (100-300) mg: (100-250) mg: (500-800) mL;

[0017] In the step (4), the ratio of the mass of the iron single-atom nanozyme, ferric acetylacetonate, and melamine to the volume of ethanol is (200-500) mg: (100-300) mg: (200-400) mg: (500-800) mL;

[0018] The annealing temperature in step (3) and step (6) is 800-1200° C., and the annealing time is 2-4 hours.

[0019] Preferably, the heating reaction temperature in step (1) and step (4) is (25-55)°C and the time is (48-72) hours. More preferably, the temperature is 25°C and the time is 48 hours.

[0020] Preferably, the centrifugal speed in step (2) and step (5) is 10000-14000 rpm, and the centrifugal time is 6-14 min. More preferably, it is 12000 rpm, and the centrifugal time is 10 min.

[0021] Preferably, the drying temperature in step (2) and step (5) is 50-70°C and the drying time is 24-48 hours. More preferably, the drying temperature is 50°C and the drying time is 24 hours.

[0022] Preferably, in step (3) and step (6), annealing is performed under an argon protective atmosphere, and the heating rate is (2-4)°C / min. More preferably, it is 2°C / min.

[0023] Preferably, the method comprises the following steps:

[0024] (1) Dissolve 3 g zinc nitrate, 100 mg ferric acetylacetonate and 100 mg 2-methylimidazole in 500 mL ethanol and react at 25 °C for 48 h under stirring;

[0025] (2) The solution after the reaction in step (1) was centrifuged at 12000 rpm for 10 min, and the precipitate was washed with ethanol and deionized water for multiple times until the supernatant was colorless; the obtained precipitate was dried under vacuum at 50° C. for 24 h to obtain a reddish brown solid powder;

[0026] (3) placing the powder obtained in step (2) in an alumina quartz crucible, and performing high temperature annealing in a tube furnace at a heating rate of 2°C / min, annealing at 1000°C for 3h, and then cooling naturally to room temperature. The whole process is carried out under argon gas; placing the obtained black powder in a quartz mortar and grinding it thoroughly to obtain a black powder, which is an iron single atom nanopowder;

[0027] (4) 200 mg of the powder obtained in step (3) was dissolved in 500 mL of ethanol with 100 mg of ferric acetylacetonate and 200 mg of melamine. The mixture was stirred at 25° C. for 48 h.

[0028] (5) The solution after the reaction in step (4) was centrifuged at 12000 rpm for 10 min, and the precipitate was washed with ethanol and deionized water for multiple times until the supernatant was colorless; the obtained precipitate was dried under vacuum at 50° C. for 24 h to obtain a powder;

[0029] (6) placing the powder obtained in step (5) in an alumina quartz crucible, and performing high temperature annealing in a tube furnace at a heating rate of 2°C / min, annealing at 1000°C for 3h, and then cooling naturally to room temperature. The whole process is carried out under argon gas; placing the obtained black powder in a quartz mortar and grinding it thoroughly to obtain a black powder, which is an iron diatomic nanopowder.

[0030] The present invention also proposes an iron diatomic nanozyme prepared by the above preparation method.

[0031] The present invention also proposes an application of the iron diatomic nanozyme as a catalase in enhancing the resistance to oxidative stress in a living body.

[0032] The beneficial effects of the present invention are:

[0033] (1) The present invention specifically uses ferric acetylacetonate as an iron source, ethanol as a solvent, zinc nitrate, 2-methylimidazole, and melamine as carbon and nitrogen sources, and obtains a structurally stable iron diatomic nanozyme through high-temperature annealing. The nanozyme has a stable configuration and good biocompatibility. It also has the antioxidant catalytic activity of catalase (CAT), and can be applied to antibacterial and anti-inflammatory, tumor treatment, pollution degradation, etc.

[0034] (2) Compared with other single-atom iron nanozymes, the diatomic iron nanozymes synthesized in the present invention can more efficiently convert H 2 O 2 Decompose into O 2 and H 2 O, greatly reducing the level of oxidative stress at the site of inflammation, thereby greatly improving the treatment efficiency of the site of inflammation.

[0035] (3) Compared with other methods, the raw materials used in the present invention are low in cost and safe, the synthesis conditions are mild, the synthesis steps are simple, and a large amount of iron diatomic nanozymes can be synthesized in a short period of time. It has great prospects for application in large-scale industrial manufacturing in the future.

[0036] (4) The nanozyme has high biocompatibility and structural stability. Due to its unique physicochemical properties, low cost, good stability, and excellent cellular antioxidant enzyme activity, the nanozyme becomes a new candidate for the treatment of diseases caused by oxidative stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1These are transmission electron microscopy characterization images of the iron diatomic nanozyme at different resolutions in Example 1 of the present invention. Figure 1 a is a transmission electron microscopy image of the iron diatomic nanozyme at a resolution of 200 nm. Figure 1 b is a transmission electron microscopy image of the iron diatom nanozyme at a resolution of 50 nm;

[0038] Figure 2 The particle size distribution of the iron diatomic nanozyme in Example 1 of the present invention;

[0039] Figure 3 HAADF and element mapping images of the iron diatom nanozyme in Example 1 of the present invention;

[0040] Figure 4 This is a spherical aberration electron microscope image of the iron diatomic nanozyme in Example 1 of the present invention;

[0041] Figure 5 is the distance image between the two atoms in the iron diatomic nanozyme in Example 1 of the present invention, Figure 5 a is Figure 4 The red circle in the middle marks the distance between the two atoms that are closer. Figure 5 b is Figure 4 The middle blue circle marks the distance between two atoms that are farther apart;

[0042] Figure 6 This is an X-ray mapping image of the iron diatom nanozyme in Example 1 of the present invention;

[0043] Figure 7 This is a Raman characterization image of the iron diatomic nanozyme in Example 1 of the present invention;

[0044] Figure 8 is the specific surface area of ​​the iron diatomic nanozyme in Example 1 of the present invention ( Figure 8 a) and pore size ( Figure 8 b) images;

[0045] Fig. 9 is the X-ray photoelectron spectrum of the iron diatomic nanozyme in Example 1 of the present invention;

[0046] Fig.10 is the N 1s spectrum of the X-ray photoelectron spectrum of the iron diatomic nanozyme in Example 1 of the present invention;

[0047] Fig.11 This is the non-metallic X-ray synchrotron radiation N spectrum image of the iron diatomic nanozyme in Example 1 of the present invention;

[0048] Fig.12 is the Fe 2p spectrum of the X-ray photoelectron spectrum of the iron diatomic nanozyme in Example 1 of the present invention;

[0049] Fig.13 This is the K-edge analysis spectrum of the synchrotron radiation Fe element of the iron diatomic nanozyme in Example 1 of the present invention;

[0050] Fig.14 This is the R space analysis spectrum of the synchrotron radiation Fe element of the iron diatomic nanozyme in Example 1 of the present invention;

[0051] Fig.15 This is the R space fitting spectrum of the synchrotron radiation Fe element of the iron diatomic nanozyme in Example 1 of the present invention;

[0052] Fig.16 This is the K-space fitting spectrum of the synchrotron radiation Fe element of the iron diatomic nanozyme in Example 1 of the present invention;

[0053] Fig.17 This is an image of the long-term stability of the iron diatom nanozyme in solution in Example 1 of the present invention;

[0054] Fig.18 This is the infrared spectrum of the iron diatom nanozyme in Example 1 of the present invention;

[0055] Fig.19 For the present invention in H 2 O 2 The solution was added with the iron diatomic nanozyme in Example 1 before and after the generation of O 2 Comparison chart of bubbles; Fig.19 a is H 2 O 2 Image of the solution without the addition of iron diatomic nanozyme; Fig.19 a is H 2 O 2 The solution was added with the iron diatomic nanozyme of Example 1 to generate O 2 Bubble chart;

[0056] Fig. 20 The in vitro catalase activity evaluation of the iron diatom nanozyme in Example 1 of the present invention is as follows: Fig. 20 a is the absorbance change at 240 nm during the catalytic decomposition of hydrogen peroxide in Example 1, Fig. 20 b is the dissolved oxygen generated in the hydrogen peroxide solution in Example 1;

[0057] Fig.21 Schematic diagram of the synthesis principle of the iron diatom nanozyme in Example 1 of the present invention;

[0058] Fig. 22 The physical phase and morphology characterization of the iron single-atom nanozyme in Comparative Example 1 of the present invention are as follows: Fig. 22 a is the X-ray diffraction image of the sample of Comparative Example 1, Fig. 22 b is the transmission electron microscope image of the sample of comparative example 1, Fig. 22 c is the spherical aberration electron microscope image of the sample of comparative example 1;

[0059] Fig.23 The iron single-atom nanozyme in comparative example 1 of the present invention and the iron diatomic nanozyme in example 1 are 2 O 2 O is generated in the solution 2 Bubble comparison chart, Fig.23 a is H 2 O 2 Image of the solution without any nanozymes added; Fig.23 b is H 2 O 2 The solution was added with the iron single-atom nanozyme of comparative example 1 to generate O 2 Bubble chart, Fig.23 c is H 2 O 2 The solution was added with the iron diatomic nanozyme of Example 1 to generate O 2 Bubble chart;

[0060] Fig.24 The in vitro catalase activity evaluation of the iron single-atom nanozyme in Comparative Example 1 of the present invention is as follows: Fig.24 a is the absorbance change at 240 nm during the decomposition of hydrogen peroxide catalyzed by Comparative Example 1, Fig.24 b is the dissolved oxygen generated in the hydrogen peroxide solution in Comparative Example 1;

[0061] Fig.25 The physical phase and morphology characterization of the iron single-atom nanozyme in Comparative Example 2 of the present invention are as follows: Fig.25 a is the X-ray diffraction image of the sample of comparative example 2, Fig.25 b is the transmission electron microscope image of the sample of comparative example 2, Fig.25 c is the spherical aberration electron microscope image of the sample of comparative example 2;

[0062] Fig.26 The iron single-atom nanozyme in comparative example 2 of the present invention and the iron diatomic nanozyme in example 1 are 2 O 2 O is generated in the solution 2 Bubble comparison chart, Fig.26 a is H 2 O 2 Image of the solution without any nanozymes added; Fig.26 b is H 2 O 2 The solution was added with the iron single-atom nanozyme of comparative example 2 to generate O 2 Bubble chart, Fig.26 c is H 2 O 2 The solution was added with the iron diatomic nanozyme of Example 1 to generate O 2Bubble chart;

[0063] Fig. 27 The in vitro catalase activity evaluation of the iron single-atom nanozyme in Comparative Example 2 of the present invention is as follows: Fig. 27 a is the absorbance change at 240 nm during the decomposition of hydrogen peroxide catalyzed by Comparative Example 2, Fig. 27 b is the dissolved oxygen generated in the hydrogen peroxide solution in Comparative Example 2;

[0064] Fig.28 The physical phase and morphology characterization of the iron cluster nanozyme in Comparative Example 3 of the present invention are as follows: Fig.28 a is the X-ray diffraction image of the sample of comparative example 3, Fig.28 b is the transmission electron microscope image of the sample of comparative example 3, Fig.28 c is the spherical aberration electron microscope image of the sample of comparative example 3;

[0065] Fig.29 The iron cluster nanozyme in comparative example 3 of the present invention and the iron diatomic nanozyme in example 1 are 2 O 2 O is generated in the solution 2 Bubble comparison chart, Fig.29 a is H 2 O 2 Image of the solution without any nanozymes added; Fig.29 b is H 2 O 2 The solution was added with the iron cluster nanozyme of comparative example 3 to generate O 2 Bubble chart, Fig.29 c is H 2 O 2 The solution was added with the iron diatomic nanozyme of Example 1 to generate O 2 Bubble chart;

[0066] Fig.30 The in vitro catalase activity evaluation of the iron cluster nanozyme in Comparative Example 3 of the present invention is as follows: Fig.30 a is the absorbance change at 240 nm during the catalytic decomposition of hydrogen peroxide in Comparative Example 3, Fig.30 b is the dissolved oxygen generated in the hydrogen peroxide solution in Comparative Example 3. DETAILED DESCRIPTION

[0067] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0069] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0070] Embodiment 1:

[0071] A method for preparing an iron diatomic nanozyme comprises the following steps:

[0072] Step 1: weigh 3 g zinc nitrate, 100 mg ferric acetylacetonate, 100 mg 2-methylimidazole and 500 mL ethanol in a beaker, stir on a magnetic stirrer at 25 °C for 72 h;

[0073] Step 2: The solution obtained in step 1 is centrifuged at 12000 rpm for 10 min, and the precipitate is washed with ethanol and deionized water for multiple times until the supernatant is colorless; finally, the precipitate at the bottom of the test tube is dried at 50° C. under vacuum for 48 h to obtain a reddish brown powder;

[0074] Step 3: Take the reddish brown powder obtained in step 2 and perform high temperature annealing in a tube furnace at a heating rate of 2°C / min, perform high temperature annealing at 1000°C for 3 hours, and then cool naturally to room temperature. The whole process is carried out under argon. Finally, put the obtained black powder in a quartz mortar and grind it thoroughly to obtain the black powder, which is the iron single atom nanopowder;

[0075] Step 4: Dissolve 200 mg of the powder obtained in step 3, 100 mg of ferric acetylacetonate and 200 mg of melamine in 500 mL of ethanol and react at 25° C. for 48 h under stirring;

[0076] Step 5: Centrifuge the solution after the reaction in step 4 at 12000 rpm for 10 min, take out the precipitate and wash it with ethanol and deionized water several times until the supernatant becomes colorless; dry the obtained precipitate at 50°C under vacuum for 24 h to obtain a powder, which is the precursor for preparing the diatomic nanozyme;

[0077] Step 6: Place the powder obtained in step 5 in an alumina quartz crucible and perform high-temperature annealing in a tube furnace at a heating rate of 2°C / min. Perform high-temperature annealing at 1000°C for 3 hours, and then cool naturally to room temperature. The entire process is carried out under argon. Place the obtained black powder in a quartz mortar and grind it thoroughly to obtain a black powder, which is an iron diatomic nanopowder.

[0078] Embodiment 2:

[0079] A method for preparing an iron diatomic nanozyme comprises the following steps:

[0080] Step 1: Weigh 4 g zinc nitrate, 200 mg ferric acetylacetonate, 200 mg 2-methylimidazole and 600 mL ethanol in a beaker, stir on a magnetic stirrer at 55 °C for 48 h;

[0081] Step 2: Centrifuge the solution obtained in step 1 at 10,000 rpm for 14 minutes, take the precipitate and wash it with ethanol and deionized water several times until the supernatant becomes colorless. Finally, dry the precipitate at the bottom of the test tube at 60°C under vacuum for 30 hours to obtain a reddish-brown powder, which is the precursor for preparing diatomic nanozymes;

[0082] Step 3: Take the reddish brown powder obtained in step 2 and perform high temperature annealing in a tube furnace at a heating rate of 4°C / min, perform high temperature annealing at 1200°C for 2.5h, and then cool naturally to room temperature. The whole process is carried out under argon. Finally, put the obtained black powder in a quartz mortar and grind it thoroughly to obtain the black powder, which is the iron single atom nanopowder;

[0083] Step 4: Dissolve 400 mg of the powder obtained in step 3, 150 mg of ferric acetylacetonate and 300 mg of melamine in 650 mL of ethanol and react at 55° C. for 48 h under stirring;

[0084] Step 5: Centrifuge the solution after the reaction in step 4 at 12000 rpm for 10 min, take out the precipitate and wash it with ethanol and deionized water several times until the supernatant becomes colorless; dry the obtained precipitate at 50°C under vacuum for 24 h to obtain a powder, which is the precursor for preparing the diatomic nanozyme;

[0085] Step 6: Place the powder obtained in step 5 in an alumina quartz crucible and perform high-temperature annealing in a tube furnace at a heating rate of 4°C / min. Perform high-temperature annealing at 1200°C for 2.5 hours, and then cool naturally to room temperature. The entire process is carried out under argon. Place the obtained black powder in a quartz mortar and grind it thoroughly to obtain a black powder, which is an iron diatomic nanopowder.

[0086] Embodiment 3:

[0087] A method for preparing an iron diatomic nanozyme comprises the following steps:

[0088] Step 1: Weigh 5 g zinc nitrate, 300 mg ferric acetylacetonate, 250 mg 2-methylimidazole and 800 mL ethanol in a beaker, stir on a magnetic stirrer at 40 °C for 55 h;

[0089] Step 2: Centrifuge the solution obtained in step 1 at 14,000 rpm for 6 minutes, take the precipitate and wash it with ethanol and deionized water several times until the supernatant is colorless. Finally, dry the precipitate at the bottom of the test tube at 70°C under vacuum for 24 hours to obtain a reddish-brown powder, which is the precursor for preparing diatomic nanozymes;

[0090] Step 3: Take the reddish brown powder obtained in step 2 and perform high temperature annealing in a tube furnace at a heating rate of 3°C / min, anneal at 800°C for 4 hours, and then cool naturally to room temperature. The whole process is carried out under argon. Finally, put the obtained black powder in a quartz mortar and grind it thoroughly to obtain the black powder, which is the iron single atom nanopowder;

[0091] Step 4: Dissolve 500 mg of the powder obtained in step 3, 300 mg of ferric acetylacetonate and 400 mg of melamine in 800 mL of ethanol and react at 40° C. for 55 h under stirring;

[0092] Step 5: Centrifuge the solution after the reaction in step 4 at 12000 rpm for 10 min, take out the precipitate and wash it with ethanol and deionized water several times until the supernatant becomes colorless; dry the obtained precipitate at 50°C under vacuum for 24 h to obtain a powder, which is the precursor for preparing the diatomic nanozyme;

[0093] Step 6: Place the powder obtained in step 5 in an alumina quartz crucible and perform high-temperature annealing in a tube furnace at a heating rate of 3°C / min. Perform high-temperature annealing at 800°C for 4 hours, and then cool naturally to room temperature. The entire process is carried out under argon. Place the obtained black powder in a quartz mortar and grind it thoroughly to obtain a black powder, which is an iron diatomic nanopowder.

[0094] Comparative Example 1: Preparation of Iron Single Atom Nanozyme

[0095] The difference between this comparative example and Example 1 is that: Step 1: 20 mg of ferric acetylacetonate, and the rest is the same as Example 1.

[0096] The product obtained in this comparative example has an X-ray diffraction pattern as shown in Fig. 22 Its transmission electron microscope image and spherical aberration electron microscope image are shown in a. Fig. 22 b, as shown in 22c.

[0097] Comparative Example 2: Preparation of Iron Single Atom Nanozyme

[0098] The difference between this comparative example and Example 1 is that: Step 3: high temperature annealing at 700° C., and the rest is the same as Example 1.

[0099] The product obtained in this comparative example has an X-ray diffraction pattern as shown in Fig.25Its transmission electron microscope image and spherical aberration electron microscope image are shown in a. Fig.25 b, as shown in 25c.

[0100] Comparative Example 3: Preparation of iron cluster nanozymes

[0101] The difference between this comparative example and Example 1 is that: Step 3: annealing at 1000° C. for 5 h, and the rest is the same as Example 1.

[0102] The product obtained in this comparative example has an X-ray diffraction pattern as shown in Fig.28 Its transmission electron microscope image and spherical aberration electron microscope image are shown in a. Fig.28 b, as shown in 28c.

[0103] First, the morphology of the iron diatomic nanozyme prepared in Example 1 was characterized. Figure 1 As shown, the sample observed by transmission electron microscopy is in the form of flakes with a diameter of about 200 nm.

[0104] like Figure 2 As shown, the particle size distribution test of the samples in Example 1 shows that the size distribution of most samples is around 181.3 nm.

[0105] The high angle annular dark field (HAADF) image of the iron diatomic nanozyme in Example 1 and the distribution (mapping) image of the elements contained are shown in FIG. Figure 3 As shown, it can be seen from the figure that the three elements Fe, C and N are evenly distributed in the sample.

[0106] The spherical aberration electron microscope image of the nanozyme in Example 1 is as follows Figure 4 As shown, iron atoms appear in pairs and evenly, indicating that the iron atoms in the sample exist in the form of diatoms.

[0107] like Figure 5 As shown, by measuring the distance between adjacent iron atoms, it is shown that the distance between atoms is between 2.32 Å and 2.69 Å.

[0108] The X-ray diffraction pattern of the iron diatomic nanozyme in Example 1 is as follows: Figure 6 As shown in the figure, the spectrum clearly shows the characteristic diffraction peaks of the iron diatomic nanozyme. Specifically, the peaks at 26.3° and 43.1° correspond to the (002) and (100) crystal planes of graphite carbon, respectively. No diffraction peaks related to the crystal form of iron were found on this spectrum, indicating that iron exists in the form of atomic dispersion. Figure 1-6 The successful preparation of iron diatom nanozymes was demonstrated.

[0109] like Figure 7As shown, the Raman test analysis was performed on the iron diatomic nanozyme in Example 1. The D peak in the spectrum represents the defect peak of disordered carbon, and the G peak represents the degree of graphitization. D / I G The ratio is close to 1.0, indicating that the degree of graphitization of carbon in the sample is good.

[0110] like Figure 8 As shown, the specific surface area of ​​the iron diatomic nanozyme in Example 1 is 890.1 m 2 / g, and the average pore size is 3.4nm, indicating that the iron diatom nanozyme has a large specific surface area and a porous structure.

[0111] like Fig. 9 As shown, the full X-ray photoelectron spectrum of the iron diatomic nanozyme in Example 1 shows that the sample of Example 1 is composed of four elements: C, O, N and Fe, and their atomic percentages are 87.40%, 0.07%, 5.81% and 0.64%, respectively.

[0112] The N 1s spectrum of the iron diatomic nanozyme X-ray photoelectron spectroscopy in Example 1 is as follows: Fig.10 As shown, the atomic percentages of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen are 45.86%, 16.03% and 16.70%, respectively.

[0113] The spectrum of N in the non-metal synchrotron radiation of the iron diatomic nanozyme in Example 1 is as follows Fig.11 As shown, Fig.10 The results shown are consistent, and the signal of the pyridine nitrogen characteristic peak is the strongest, indicating that the pyridine nitrogen content in the sample accounts for the highest proportion.

[0114] The Fe 2p spectrum of the iron diatomic nanozyme X-ray photoelectron spectroscopy in Example 1 is as follows: Fig.12 As shown, only a weak signal appears in the spectrum, which is different from Figure 6 This corresponds to the results in , which once again shows that the iron in the nanozyme exists in an atomically dispersed form.

[0115] like Fig.13 As shown, the synchrotron radiation Fe K-edge of the iron diatomic nanozyme in Example 1 shows that near the front peak of the edge, the K-edge line of the nanozyme Fe is between Fe 3 O 4 and Fe foil, indicating that the valence state of Fe is between 0 and +3.

[0116] like Fig.14 As shown, the R space of the synchrotron radiation Fe of the iron diatomic nanozyme in Example 1 shows that there is a Fe-N bond near 1.5Å and a Fe-Fe bond near 2.4Å, confirming that the iron in the sample exists in a diatomic dispersed form on the CN skeleton.

[0117] like Fig.15 As shown, by fitting the synchrotron radiation R space data of the iron diatomic nanozyme in Example 1, it is clear that the specific internal structure of the sample in Example 1 is Fe 2 N 6 Configuration of diatomic nanozymes.

[0118] like Fig.16 As shown, the K-space data of the iron diatomic nanozyme in Example 1 is fitted, showing that the data fit is very good, which once again verifies the Fe 2 N 6 Configuration.

[0119] The hydration kinetics particle size measurement results of the iron diatomic nanozyme in Example 1 over a 30-day period are as follows: Fig.17 As shown in the figure, the material size did not change significantly during the cycle. This indicates that the sample maintained good dispersion for a long time without significant agglomeration, thus proving its excellent stability.

[0120] like Fig.18 As shown in FIG. 1 , the infrared test of the iron diatomic nanozyme in Example 1 was performed using a Fourier infrared spectrometer. The absorption peak positions of different wavelengths in the figure represent the different functional group bond positions. -1 The peak represents -OH stretching vibration, 1635 cm -1 The peak position represents CC bending vibration, 1120 cm -1 The peak position represents the bending vibration of -OH. The appearance of -OH also shows to a certain extent that the sample has good water solubility.

[0121] like Fig.19 As shown, the sample of Example 1 can generate a large number of bubbles in the hydrogen peroxide solution, indicating that it has excellent catalase activity and can quickly decompose hydrogen peroxide into oxygen.

[0122] The monitoring of the decomposition process of hydrogen peroxide and the monitoring of the dissolved oxygen content are respectively as follows: Fig. 20 The results show that the iron diatomic nanozyme in Example 1 effectively catalyzes the decomposition of hydrogen peroxide and the generation of oxygen, respectively.

[0123] Figure 19-20 The specific experimental methods are as follows:

[0124] Hydrogen peroxide decomposition detection: Use UV spectrophotometer to detect H 2 O 2 The iron diatomic nanozyme sample (10 μg / mL) in Example 1 was mixed with 3 mL of H 2 O 2The solutions (10 mM) were mixed in a cuvette, and the absorbance change of the reaction system at 240 nm was measured continuously at 37 °C for 10 min.

[0125] Oxygen generation detection: The iron diatomic nanozyme (10 μg / mL) prepared in Example 1 was dispersed in 100 mM H 2 O 2 In the solution, bubbles were observed after 5 minutes of reaction at 37 °C. In addition, the iron diatomic nanozyme (2 μg / mL) in Example 1 was mixed with 5 mL of H 2 O 2 The aqueous solutions (100 mM) were mixed under gentle stirring, and the dissolved oxygen concentration was monitored on a multiparameter analyzer using a specific oxygen electrode.

[0126] The iron diatomic nanozyme obtained by the present invention is prepared by reacting zinc nitrate, ferric acetylacetonate, 2-methylimidazole and ethanol, and has a structure-guided and more efficient catalase anti-oxidative stress therapeutic effect. The schematic diagram of the principle is shown in the figure Fig.21 shown.

[0127] Comparative Example 1 synthesized an iron single-atom nanozyme with extremely low single-atom content by reducing the amount of iron source, i.e., ferric acetylacetonate, at the same annealing temperature and performing annealing treatment for the same time. Fig. 22 a is the X-ray diffraction pattern of comparative example 1. The sample of comparative example 1 still presents the same XRD characteristic peaks as the sample of embodiment 1. Fig. 22 The characteristic peaks of graphite carbon are also shown in a, but the characteristic peaks of iron are not present. Specifically, the peaks at 26.3° and 43.1° correspond to the (002) and (100) crystal planes of graphite carbon, respectively. Fig. 22 b is a transmission electron microscope image of comparative example 1. The sample of comparative example 1 still presents the same morphology and structure as the sample of embodiment 1. Fig. 22 c is the spherical aberration electron microscope image of the sample in comparative example 1. The iron atoms shown in the image are sparsely distributed and the content is much lower than that in example 1. Figure 23-24 The catalase activity of comparative example 1 is evaluated. At the same concentration, the rate at which the sample of comparative example 1 decomposes hydrogen peroxide into oxygen is much lower than that of example 1, indicating that the content of metal active catalytic sites in comparative example 1 is much lower than that in example 1. The above data fully demonstrate that at the same annealing temperature, reducing the amount of ferric acetylacetonate can only obtain single-atom nanozymes, confirming the necessity of controlling the amount of iron source for obtaining iron diatomic nanozymes.

[0128] Comparative Example 2 synthesized an iron single-atom nanozyme with a higher single-atom content by setting the annealing temperature to 700°C and performing annealing treatment for the same time under the same raw material ratio. Fig.25a is the X-ray diffraction pattern of Comparative Example 2. The sample of Comparative Example 2 still presents the same XRD characteristic peaks as the sample of Example 1. Fig.25 The characteristic peaks of graphite carbon are also shown in a, but the characteristic peaks of iron are not present. Specifically, the peaks at 26.3° and 43.1° correspond to the (002) and (100) crystal planes of graphite carbon, respectively. Fig.25 b is a transmission electron microscope image of comparative example 2. The sample of comparative example 2 still presents the same morphology and structure as the sample of embodiment 1. Fig.25 c is a spherical aberration electron microscope image of the sample in comparative example 2. The single atoms shown in the image are densely distributed, and the number is significantly increased compared with that in comparative example 1, but no iron diatoms are formed as described in Example 1. Figure 26-27 The catalase activity of comparative example 2 was evaluated. At the same concentration, the rate at which the sample in comparative example 2 decomposed hydrogen peroxide into oxygen was much lower than that in example 1, indicating that the metal active catalytic sites in comparative example 2 still existed in contrast to those in example 1. The above data demonstrate the necessity of controlling the annealing temperature for obtaining iron diatomic nanozymes.

[0129] Comparative Example 3 synthesized iron cluster nanozymes with the same raw material ratio but different annealing time. Fig.28 a is the X-ray diffraction pattern of comparative example 3, which is different from the sample of example 1 in that: Fig.28 Although the characteristic peaks of graphite carbon are also shown in a, the characteristic peaks of iron appear. Specifically, the peaks at 26.3°, 43.1°, 42.9° and 44.7° correspond to the (002) and (100) crystal planes of graphite carbon and the (100) and (101) crystal planes of iron, respectively. Fig.28 b is a transmission electron microscope image of comparative example 3. Compared with the sample in example 1, the structure has changed significantly. Hollow structures and black spots have appeared on the surface of the sample, indicating that graphitization is serious. Fig.28 c is the spherical aberration electron microscope image of the sample in comparative example 3. The diatomic morphology in the image becomes blurred and a large area of ​​bright spots appears, indicating that the iron cluster nanozyme synthesized in comparative example 3 is obtained. Figure 29-30 It is also proved that the catalase activity of the sample in comparative example 3 is lower than that in example 1. The above data fully demonstrate that increasing the annealing time will damage the structure of the diatomic structure, thereby proving the necessity of a suitable reaction time for obtaining the iron diatomic nanozyme.

[0130] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an iron diatomic nanozyme, characterized in that: The following steps are involved: (1) Dissolve zinc nitrate, ferric acetylacetonate and 2-methylimidazole in ethanol and heat to react; (2) centrifuging the solution after the reaction in step (1), taking out the precipitate, washing it, and drying it to obtain a reddish brown solid powder; (3) annealing and grinding the powder obtained in step (2) to obtain an iron single-atom nanozyme; (4) dissolving the iron single-atom nanozyme obtained in step (3), ferric acetylacetonate and melamine in ethanol and heating them for reaction; (5) centrifuging the solution after the reaction in step (4), taking out the precipitate, washing it, and drying it to obtain a powder; (6) annealing and grinding the powder obtained in step (5) to obtain an iron diatom nanozyme; In the step (1), the ratio of the mass of zinc nitrate, ferric acetylacetonate, and 2-methylimidazole to the volume of ethanol is 3-6 g: 100-300 mg: 100-250 mg: 500-800 mL; In the step (4), the ratio of the mass of the iron single-atom nanozyme, ferric acetylacetonate, and melamine to the volume of ethanol is 200-500 mg: 100-300 mg: 200-400 mg: 500-800 mL; The annealing temperature in step (3) and step (6) is 800-1200° C., and the annealing time is 2-4 hours.

2. The method for preparing the iron diatomic nanozyme according to claim 1, characterized in that: The heating reaction temperature in step (1) and step (4) is 25-55° C. and the time is 48-72 hours.

3. The method for preparing the iron diatomic nanozyme according to claim 1, characterized in that: In the steps (2) and (5), the centrifugal speed is 10000-14000 rpm, and the centrifugal time is 6-14 min.

4. The method for preparing the iron diatomic nanozyme according to claim 3, characterized in that: The centrifugal speed in step (2) and step (5) is 12000 rpm, and the centrifugal time is 10 min.

5. The method for preparing the iron diatomic nanozyme according to claim 1, characterized in that: The drying temperature in step (2) and step (5) is 50-70° C. and the drying time is 24-48 hours.

6. The method for preparing the iron diatomic nanozyme according to claim 5, characterized in that: The drying temperature in step (2) and step (5) is 50° C. and the drying time is 24 h.

7. The method for preparing the iron diatomic nanozyme according to claim 1, characterized in that: In the steps (3) and (6), annealing is performed under an argon protective atmosphere, with a heating rate of 2-4°C / min.

8. The method for preparing the iron diatomic nanozyme according to claim 7, characterized in that: In the steps (3) and (6), annealing is performed under an argon protective atmosphere, with a heating rate of 2°C / min.

9. The method for preparing the iron diatomic nanozyme according to claim 1, characterized in that: The following steps are involved: (1) Dissolve 3 g zinc nitrate, 100 mg ferric acetylacetonate and 100 mg 2-methylimidazole in 500 mL ethanol and react at 25 °C for 48 h under stirring; (2) The solution after the reaction in step (1) was centrifuged at 12000 rpm for 10 min, and the precipitate was washed with ethanol and deionized water for multiple times until the supernatant was colorless; the obtained precipitate was dried under vacuum at 50° C. for 24 h to obtain a reddish brown solid powder; (3) placing the powder obtained in step (2) in an alumina quartz crucible, and performing high temperature annealing in a tube furnace at a heating rate of 2°C / min, annealing at 1000°C for 3h, and then cooling naturally to room temperature. The whole process is carried out under argon gas; placing the obtained black powder in a quartz mortar and grinding it thoroughly to obtain a black powder, which is an iron single atom nanopowder; (4) 200 mg of the powder obtained in step (3) was dissolved in 500 mL of ethanol with 100 mg of ferric acetylacetonate and 200 mg of melamine. The mixture was stirred at 25° C. for 48 h. (5) The solution after the reaction in step (4) was centrifuged at 12000 rpm for 10 min, and the precipitate was washed with ethanol and deionized water for multiple times until the supernatant was colorless; the obtained precipitate was dried under vacuum at 50° C. for 24 h to obtain a powder; (6) placing the powder obtained in step (5) in an alumina quartz crucible, and performing high temperature annealing in a tube furnace at a heating rate of 2°C / min, annealing at 1000°C for 3h, and then cooling naturally to room temperature. The whole process is carried out under argon gas; placing the obtained black powder in a quartz mortar and grinding it thoroughly to obtain a black powder, which is an iron diatomic nanopowder.

10. The iron diatom nanozyme obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Plant microenvironment response type diatomic nano-enzyme as well as preparation method and application thereof

    CN116510777A

  • Synthesis of Mn / Fe Prussian Blue Analogues and Investigation on Its Catalytic Activity

    AU2019101135A4

  • Method for rapidly detecting cefalexin and lead by diatomic nano enzyme base

    CN116519681A